Students’ Critical and Creative Thinking Skills through Inquiry and Discovery Learning Models in Social Studies Learning Class VIII Mts Negeri 1 Lebong - M. Thoha; Hilyati Milla; Risnanosanti (Edumaspul: Jurnal Pendidikan, 2026)
This study aimed to determine the effect of the Inquiry model, Discovery Learning, and conventional learning models on students’ critical and creative thinking skills, In addition, this study also aimed to identify the differences in students’ critical and creative thinking skills among students taught using these three models at Mts Negeri 1 Lebong. This research employed a quasi-experimental design. The population of this study consisted of all eight-grade students of MTs Negeri 1 Lebong. The sampling technique used was cluster random sampling, resulting in three sample classes: a class taught using the Inquiry model, a class using Discovery Learning, and a class using conventional learning, with a total sample 106 students. The research instrument was a test designed students’ critical and creative thinking skills. Data analysis was conducted using the One-Way ANOVA test followed by the Least Significant Difference (LSD) post hoc test. The results of the study showed that there was a significant effect of the Inquiry model, Discovery Learning, and conventional learning models on students’ critical and creative thinking skills. Furthermore, there were significant differences in students’ critical and creative thinking skills abilities among the classes taught using the Inquiry model, Discovery Learning, and conventional learning. The guided Discovery Learning model was found to be more effective in improving students’ critical thinking skills, while the Inquiry and Discovery Learning models were more effective in improving students’ creative thinking skills. Therefore, the implementation of the Inquiry and Discovery Learning models can serve as effective alternative learning models to improve students’ critical and creative thinking skills compared to conventional learning